Dietotherapy in children with obesity associated with adult lactase deficiency - A.E. Abaturov; A.A. Nikulina; D.V. Logvinov; P.A. Kolbasin (Zaslavsky O.Yu., 2017)
Background. Excess lactose in the infant's nutrition, especially in combination with adult lactase deficiency (С/C 13910 genotype), promotes the persistence of a chronic inflammatory process associated with the formation of obesity-complicated insulin resistance. Low-lactose dietotherapy reduces insulin resistance, contributes to the immunosuppressive orientation of the immune response due to the absence of lactose-dependent inhibition of galectin 9 - the main ligand of the T-cell apoptosis receptor (Tim-3). The purpose of the study was to evaluate the effectiveness of the low-lactose diet, which was formed using the computer program "Low-lactose diet", in the treatment of obesity associated with adult lactase deficiency in children aged 6-18 years. Materials and methods. According to the results of the study of polymorphisms of the lactase gene (SNP LCT), out of 80 children aged 6-18 years with obesity, a group of children (n = 38) was isolated with C/C 13910 genotype corresponding to adult lactase deficiency. All children were divided into two clinical groups that did not differ in number (n = 19), age, sex, and the degree of clinical manifestations of lactose malabsorption. All patients received standard therapy for the underlying disease. In addition, a low-lactose diet calculated with the help of the computer program "Low-lactose diet" created by us was prescribed to the children of the main group. The effectiveness of treatment was assessed by anthropometric and metabolic criteria. Results. The mean value of body mass index (BMI) in children of the main and comparison groups at baseline was 98.00 ± 0.52 and 97.00 ± 0.61 percentiles, respectively. After the treatment, there was a significant decrease in BMI in children of both groups (p < 0.05). The mean values of the insulin resistance index (HOMA-IR) in children of the main and comparison groups before treatment were 6.8 ± 0.3 and 5.7 ± 0.9, and after treatment - 4.4 ± 0.3 and 4.3 ± 0.8, respectively. Insulin resistance significantly (p < 0.05) decreased after a six-month treatment only under strict control of the lactose content in the diet, which was carried out using the computer program "Low-lactose diet". Conclusions. The low-lactose diet calculated with the help of the computer program "Low-lactose diet" improves the effectiveness of obesity treatment in children with C/C 13910 genotype and increases the sensitivity of tissues to insulin, thereby probably preventing the development of complications associated with insulin resistance.